Mastery of physical literacy, physical activity, and physical fitness: A comparative study of Elementary School and Madrasah Ibtidaiah students - Khoirul Husnan; Ahmad Lani; Nurcholis Sunuyeko (Universitas Sriwijaya, 2023)
This research aims to verify the mastery of physical literacy, activity and physical fitness of elementary school and Madrasah Ibtidaiah students in the Greater Malang area. Mastery of physical literacy refers to students' understanding of concepts and knowledge related to physical fitness. Physical activity includes students' participation in physical activities that involve movement and exercise, while Perception of physical fitness refers to the way a person understands and evaluates their own level of physical fitness. This research used a comparative research design with a sample of 1,468 elementary school and religious madrasah students in Malang Raya. Data was collected through a physical literacy test that measures students' conceptual understanding and knowledge of physical fitness. In addition, a physical fitness perception questionnaire was conducted to measure students' physical fitness perceptions. The results of the research show that the physical literacy mastery of elementary school and Madrasah Ibtidaiah Malang Raya students has met the specified criteria. The sports activities of students at Elementary School and Madrasah Ibtidaiah Malang Raya do not meet the specified requirements. The physical fitness level of elementary school and Madrasah Ibtidaiah Malang Raya students does not meet the specified criteria.